Navigating the Digital Landscape: How Nahdlatul Ulama Volunteers Use Social Media for Organizational Promotion - Dony Arung Triantoro (Islam Transformatif : Journal of Islamic Studies, 2024)
This article aims to investigate how the digital volunteers of Nahdlatul Ulama (NU) utilize social media to promote the organization. The study employs a qualitative approach, gathering data through online interviews and content analysis of the Instagram account @nucreativemedia. This study will address three questions: First, what motivates digital volunteers to create the Instagram account @nucreativemedia? Second, what types of content are promoted on this account? Third, how do digital volunteers present NU content on Instagram? Based on these questions, the findings indicate that: First, the initiative to create the Instagram account @nucreativemedia is driven by the desire to counter radical and conservative Islamic movements on social media. Second, the content promoted includes NU scholars, fiqh and worship, social-political issues, and public facilities associated with NU, such as pesantren (Islamic boarding schools), hospitals, universities, and products. Third, the Instagram account @nucreativemedia enhances its content through a combination of colors, images, and audio that reflect NU culture. This promotional effort further reinforces NU's position and relevance in the online space.